Optimalisasi Potensi Wakaf Tunai sebagai Penggerak Bisnis Melalui Pengembangan Fintech Wakaf di Era Digitalisasi - Nazah, Risma Khoirun (Institut Agama Islam Negeri Ponorogo, 2022)
Nowadays technological development is progressing very rapidly. Almost every line of life has been digitalized, this can be seen by the emergence of many technology-based applications that facilitate human activities. The rise of this trend also impacts waqf, especially cash waqf. If in the past waqf was only based on land for the construction of mosques, burial ground, or educational institutions but now waqf can also be in the form of cash. One of the digitalization systems that is being developed in the field of waqf is the waqf financial technology system. The existence of this system can facilitate prospective waqf in having a waqf and can increase the interest of the community which incidentally does not intend to endowments to be interested in parenting. In addition, funds from cash waqf can drive the economy by bringing up a start-up business for those mauquf alaih. Dewasa ini, perkembangan teknologi mengalami kemajuan yang sangat pesat. Hampir di setiap lini kehidupan telah terdigitalisasi, hal tersebut dapat terlihat dengan banyaknya bermunculan aplikasi berbasis teknologi yang mempermudah aktivitas manusia. Maraknya trend tersebut juga berimbas pada wakaf, tak terkecuali wakaf tunai. Apabila dahulu wakaf hanya berbasis tanah untuk pembangunan masjid, tanah pemakaman, atau lembaga pendidikan, namun sekarang wakaf juga dapat berbentuk tunai. Salah satu sistem digitalisasi yang tengah dikembangkan pada bidang perwakafan adalah sistem Financial Technology (FinTech) wakaf. Dengan adanya sistem tersebut dapat mempermudah calon wakif dalam berwakaf serta dapat meningkatkan minat masyarakat yang semula tidak berniat untuk wakaf menjadi tertarik untuk berwakaf. Selain itu, dana hasil wakaf tunai dapat menggerakkan perekonomian dengan memunculkan suatu bisnis start-up bagi mauquf alaih.